The effect of skin thickness determined using breast CT on mammographic dosimetry - Huang, Shih-Ying (American Association of Physicists in Medicine, 2008)
The effect of breast skin thickness on dosimetry in mammography was investigated. Breast computed tomography (CT) acquisition techniques, combined with algorithms designed for determining specific breast metrics, were useful for estimating skin thickness. A radial-geometry edge detection scheme was implemented on coronal reconstructed breast CT (bCT) images to measure the breast skin thickness. Skin thickness of bilateral bCT volume data from 49 women and unilateral bCT volume data from 2 women (10 healthy women and 41 women with BIRADS 4 and 5 diagnoses) was robustly measured with the edge detection scheme. The mean breast skin thickness (±inter-breast standard deviation) was found to be 1.45±0.30 mm. Since most current published normalized glandular dose (D(gN)) coefficients are based on the assumption of a 4-mm breast skin thickness, the D(gN) values computed with Monte Carlo techniques will increase up to 18% due to the thinner skin layers (e.g., 6-cm 50% glandular breast, 28 kVp Mo–Mo spectrum). The thinner skin dimensions found in this study suggest that the current D(gN) values used for mammographic dosimetry lead to a slight underestimate in glandular dose.